Criminal liability for illegal entrepreneurship, illegal banking activity, microfinancial or collection activities: comparative legal analysis of criminal legislation of foreighn countries (Journal of actual problems of jurisprudence, 2023)
Article 26 of the Constituion of the Republic of Kazakhstan specifies the right of every person to freedom of entrepreneurial activity. Entrepreneurship at the current stage is a substantial sectore that provides citizens and state with all benefits, promotes the growth of jobs, as well as speedy progress of various industries. The significance of such activity fot the country economy represents the importance and high priority of protecting legal entrepreneurial, banking, microfinance and collection activities, as well as improving the criminal legal framework.Existence of illegal entrepreneurship, illegal banking, microfinance and collection activities in the state facilitates the occurrence of negative consequences, which include the loss by the legislator of control over a certain activity, infliction of huge damage to society, the development of shawod economy, as well as increase in the number of crime. Situation at hand requires the preparation of methods that will help effectively combat mentioned type of crime.Socially dangerous act that relates to illegal business, illegal banking, microfinance or collection activities is qualified according to the article 214 of the Criminal Code of the Republic of Kazakhstan. The disposition ofThe disposition of the concerned article has the blanket nature, the existence of concepts of an evaluative character, as well as occurrence of contradictions between regulatory legal acts that leads to the uprise of certain difficulties in the qualification of the act.Key words: illegal entrepreneurship, illegal banking activities, microfinance activities, collection activities, criminal loability, entrepreneurship, etc.